Agonistic Mourning Political Dissidence and the Women in Black - Athanasiou, Athena (Edinburgh University Press, 2022)
How might mourning turn into an event of agonistic performativity?Drawing on a range of philosophical, anthropological and political theories, Athena Athanasiou offers a new way of thinking about agonistic performativity with its critical connections to national and gender politics and alongside the political intricacies of affectivity, courage and justice. Through an ethnographic account of the urban feminist and antinationalist movement Women in Black of Belgrade during the Yugoslav wars she shows that we might understand their dissident politics of mourning as a means to refigure political life beyond sovereign accounts of subjectivity and agency
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Apr 2022)
Keywords: Philosophy; PHILOSOPHY / Political; Dissenters; Mourning customs -- Political aspects -- Serbia -- Belgrade -- History -- 20th century; Yugoslav War, 1991-1995 -- Women